Sustainable Fisheries Empowerment Strategies for Blue Swimming Crab Fishers by the Environmental Defense Fund in Margasari Village - Al Faqih Alwy; Triyanti Anugrahini (Cita konsultindo, 2025)
Rajungan (Portunus pelagicus) is one of Indonesia's leading fishery commodities with a high export value. However, the high demand and the use of destructive fishing gear have caused a decline in rajungan stocks in various location in Java sea including the East coast of Lampung. This condition impacts the sus-tainability of the livelihoods of rajungan fishers. This study describes the sustainable fishery empowerment strategies for rajungan fishers by the Environmental Defense Fund (EDF) through a qualitative approach presented descriptively. Data were collected through observation, document studies, in-depth interviews with 16 informants, and focus group discussions. The results show that EDF's empowerment strategies for fishers in Margasari Village include involving them in policy development and planning in drafting sustainable rajungan management action plans and establishing conservation areas; encouraging social and political actions by strengthening rajungan fisher groups in Margasari Village and conducting communi-ty-based monitoring to protect rajungan conservation zones; as well as raising awareness about the im-portance of sustainable rajungan management and providing training such as data collection, fishery product processing, and citizen journalism. The study suggests that EDF should involve the industry in sustainable fishery empowerment strategies to support the protection of rajungan conservation areas.